ARTISTIC PERCEPTION OF REALITY IN STORIES DETAIL AND ILLUSTRATION (American Journal of Research in Humanities and Social Sciences, 2024)
In Henry’s story "Miracle Cakes", the details increased the artistic effect. In the story "Twenty years later", the details of the landscape image also served as an important main tool in the realization of the author's goal. The details of A. Qahhor's story "Dakhshat" point to the psyche, fate, and future development of the characters. In I.Sultan's story called "Windy Night", landscape image, in particular, "wind" served as the main compositional tool as a detail. The content of N. Eshanqul's story "The Man Led by the Monkey" is reflected in the details. In the writer's story "Qultoy", it can be seen that the author compares the maple tree to Arzihol, and the maple stick to Uljon, based on scientific views.